Analysing the Effects of Healthcare Payment Policies on Poverty: A Microsimulation Study with Real-World Healthcare Data - Aaltonen Katri; Tervola Jussi; Heino Pekka (International Microsimulation Association, 2025)
In Europe, many people experience financial hardship due to healthcare payments, despite (near-)universal healthcare. In Finland and other countries, austerity has further widened the gaps in coverage through increases in patient payments. However, distributional analyses of austerity have solely concentrated on the effects of tax-benefit policies. We present a method for examining how health payment policies and tax-benefit policies affect household income in conjunction to evaluate the total effect of implemented and planned policies. We linked the national tax-benefit microsimulation model, SISU, and its nationally representative 15% sample of households in 2017 (n=826,001) with administrative real-world healthcare data (Finnish Institute for Health and Welfare Care Register for Health Care, HILMO, and Social Insurance Institution of Finland, Kela, National Health Insurance reimbursement registers). As a case study, we analysed the effects on the relative poverty risk and poverty gap during two government terms. We found that between 2011 and 2015, tax-benefit policies contributed to decreasing relative poverty, and health payment changes had no measurable effects. From 2015 to 2019, the poverty risk rate and the average gap increased due to tax-benefit policies, and health payment changes strengthened the effects by 10% to 20%. Health payments and their increases deteriorated the position of older adults; nevertheless, their poverty risk remained close to the population average. Social assistance had an important buffering effect on the under 65-year-old population. Health payment increases thus exacerbated the effects of austerity on the oldest age groups. Furthermore, based on tax-benefit analyses alone, they were relatively well-protected.